Pengaruh Strategi Pembiasaan Religius dan Lingkungan Sekolah terhadap Pembentukan Karakter Siswa - Rohmah, Nisfu Laila; Suwandi, Suwandi (YASIN, 2025)
The formation of student character through religious habituation strategies and the school environment plays a crucial role in shaping a morally upright and responsible generation. This study aims to examine the influence of religious habituation strategies and the school environment, both individually and simultaneously on character formation among students at MTs Negeri 9 Jombang. A quantitative approach was employed using an ex post facto design, with a sample of 261 students selected through random sampling. Data were collected using a 30-item questionnaire and analyzed through multiple linear regression. The findings indicate that both religious habituation strategies and the school environment have a significant partial influence on students’ character formation. Simultaneously, these variables also show a significant combined effect in strengthening student character. These results reinforce theories on the critical role of values-based education and environmental factors in shaping student personality in Islamic educational institutions. The study concludes that optimizing religious habituation programs and creating a supportive learning environment are strategic steps in fostering students’ positive character development. The implications include strengthening school policies to build a holistic educational culture within madrasahs and encouraging further research on the effectiveness of character education interventions across broader educational levels.